Proceso atención de enfermería en paciente adulto mayor de 67 años con pielonefritis. - Gavilánez Gaibor, Giscela Isamar (2021)
Pyelonephritis is an upper urinary tract infection characterized by bacterial invasion of the pelvis and renal parenchyma of one or both kidneys and which can cause life-threatening complications for the patient. In 2019, at the national level, 1948 cases of pyelonephritis were reported, of which 311 affected men and 1635 women because they are the most likely to contract this disease and others related to the urinary tract due to their urogenital anatomy. Escherichia coli is the main bacteria responsible for most cases of pyelonephritis. It is a frequent cause of bacteremia and septic shock in elderly patients. The differential diagnosis should be made with kidney stones, acute abdomen, and pelvic inflammatory disease. The objective of this work was to develop the nursing care process based on critical thinking in the assessment, diagnosis, planning, execution and evaluation for decision-making in patient care and in turn relate it to the theory of Marjory Gordon, that allows an assessment of the functional patterns that constitute a fundamental pillar in the identification of real or potential problems in individuals and the nursing model of Dorothea Orem with her theory of Self-care deficit A methodology based on bibliographic research was used from sources such as the internet, books, magazine articles that were the fundamental basis for obtaining the necessary information in the preparation of this investigative work. In conclusion, the action plans developed and applied in the nursing care process for patients with pyelonephritis will improve their health by meeting their needs and achieving therapeutic success through comprehensive and effective care.